Characterizing Pain in Varicocele and the Impact of Varicocelectomy: A Single-Center Prospective Study - Mirzazadeh, Majid; Forati, Rasadokht; Vilson, Fernandino; Colaco, Marc (Medicine and Medical Research: New Perspectives Vol. 6, 2024)
Introduction: Varicocele is found in up to 15-20% of young males. Although asymptomatic in most cases, it can present with pain, infertility, testicular atrophy, or visible swelling. Despite, some studies supporting the role of varicocelectomy in pain relief, current guidelines do not mention pain as an indication for surgery. Therefore, the application of varicocelectomy in pain relief remains somewhat controversial. Aim: The aim of the study is to analyze the characteristics of pain in patients with varicocele and the outcome of varicocelectomy surgeries on pain perception. Patient and Methods: In a 14-month period, 36 consecutive patients with pain secondary to varicocele were prospectively enrolled in this study and underwent varicocelectomy. History, physical exam, detailed explanation and scoring of pain, scrotal ultrasound, and semen analysis were evaluated before and after surgery. Pain details were assessed through a patient questionnaire which included questions about the type of pain, its location, and exacerbating and relieving factors. The severity of pain was then scored by patients based on an analog numerical scale that corresponded to their level of pain. Varicocele grading was performed based on the World Health Organization (WHO) grading scale for varicoceles. Patients were followed for one year after surgery. Results: Thirty of 36 patients completed the study with appropriate follow-up visits. Patients were 17- to 34-years-old (mean 24.5±4). In 57% of patients, pain was the only presenting symptom. Pain was described as sharp in 11 (36%), burning in 5 (17%), dull in 4 (13%), and vague and hard to explain in 10 patients (33%). Pain most commonly was experienced in scrotum, inguinal, and lower abdominal area. After surgery, 12 patients (40%) had complete relief of pain. Seven patients (23%) had significant relief; seven patients (23%) had moderate relief. Overall, 26 patients (87%) had moderate (more than 50%) to complete pain relief (P<0.005). Four patients had minimal or no improvement in pain after surgery. Conclusion: Pain related to varicocele is mainly experienced in the scrotum, inguinal, and lower abdominal area. Varicocelectomy completely or significantly resolves the pain in up to 86% of patients. Limitations: This prospective study has some limitations, including a small sample size and lack of representation across multiple institutions, both of which limit generalizability. Moreover, the subjective nature of pain makes analyzing the benefit of varicocelectomy less consistent among patients. Finally, the association between varicocele grade and severity of pain was not investigated.